IMPACT OF SOCIAL MEDIA ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES (SME) IN BAUCHI METROPOLIS - Bilyaminu, Jonah; Hope , Gorip Nenfort; Bello , Mal. Kamalu Ali (International Journal of Small and Medium Enterprises, 2025)
This study examines the impact of social media on the performance of Small and Medium Enterprises (SMEs) in Bauchi metropolis. SMEs remain a vital backbone of economic development, yet many operators still struggle with visibility, competitiveness, and customer engagement in an increasingly digital marketplace. With platforms such as Facebook, Instagram, and WhatsApp becoming essential marketing tools, this research investigates how advertising, content engagement, and digital competence influence SME performance. A survey design was employed, targeting 300 SMEs randomly selected from a population of 1,015 registered businesses in Bauchi metropolis. Data were collected through structured questionnaires and analyzed using descriptive statistics and regression analysis. Findings indicate that social media advertising significantly enhances customer reach and sales growth, while engaging content fosters trust, loyalty, and brand recognition. Furthermore, SMEs with higher levels of digital marketing competence reported improved efficiency and competitiveness. The study concludes that effective adoption of social media strategies is a key determinant of SME performance in Bauchi. It recommends that SME operators invest in professional training, content-driven marketing, and paid advertising campaigns, while government and support agencies should strengthen infrastructure and digital literacy initiatives to boost SME growth in the region. Regression analysis showed that social media advertising had a significant positive effect on SME performance (β = 0.3772, t = 17.921, p < 0.001). Content engagement (β = 0.2977, t = 13.507, p < 0.001) and digital marketing competence (β = 0.2942, t = 14.015, p < 0.001) likewise had significant positive associations with performance. The model explained approximately 72.9% of the variance in SME performance (R² = 0.729). In practical terms, these coefficients imply that a one-unit increase in social media advertising, content engagement, or marketing competence corresponds to roughly a 0.3-unit increase in SME performance. JEL Classification Codes: L26, M31, O33, L25.